XUV Opacity of Aluminum between the Cold-Solid to Warm-Plasma Transition - Vinko, S; Gregori, G; Nagler, B; Whitcher, T; Desjarlais, M; Lee, R; Audebert, P; Wark, J (2009)
We present calculations of the free-free XUV opacity of warm, solid-density aluminum at photon energies between the plasma frequency at 15 eV and the L-edge at 73 eV, using both density functional theory combined with molecular dynamics and a semi-analytical model in the RPA framework with the inclusion of local field corrections. As the temperature is increased from room temperature to 10 eV, with the ion and electron temperatures equal, we calculate an increase in the opacity in the range over which the degree of ionization is constant. The effect is less pronounced if only the electron temperature is allowed to increase. The physical significance of these increases is discussed in terms of intense XUV-laser matter interactions on both femtosecond and picosecond time-scales.